1987
DOI: 10.1209/0295-5075/4/2/017
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Glass and Domain State Properties of KTaO 3 Li

Abstract: The phase boundary between low-temperature dipole glass and ferroelectric states of K1-xLixTaO3 is proposed to lie within 0.016 < x < 0.026 according to new optical birefringence, refractive index and dielectric permittivity data. The low-x glass phases are characterized by freezing temperatures Tg < 40 K, whereas in the high-x limit random-field-induced domain states are achieved via rounded first-order transition at Tc > 40 K. The crossover concentration xc ∼ 0.022 is extrapolated from the condition Tg(xc) =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(51 citation statements)
references
References 21 publications
5
46
0
Order By: Relevance
“…Since in our measurements we resolved PNRs surface structure at LT in the absence of field it can be concluded that KLT-3% undergoes a ferroelectric phase transition probably around T = 40 K. We cannot unambiguously identify the KLT state in the temperature range of 40-80 K, presumably it can be considered as a cluster polar glass, but to understand the KLT-3% phase in this temperature range, further experiments are necessary. Our results are in a good agreement with the results of measurements of the temperature dependence of birefringence of KLT samples by W. Kleeman et al and published in [11][12][13], where it was shown that the critical Li + concentration above which Downloaded by [Florida Atlantic University] at 21:43 02 February 2015…”
Section: Discussionsupporting
confidence: 93%
“…Since in our measurements we resolved PNRs surface structure at LT in the absence of field it can be concluded that KLT-3% undergoes a ferroelectric phase transition probably around T = 40 K. We cannot unambiguously identify the KLT state in the temperature range of 40-80 K, presumably it can be considered as a cluster polar glass, but to understand the KLT-3% phase in this temperature range, further experiments are necessary. Our results are in a good agreement with the results of measurements of the temperature dependence of birefringence of KLT samples by W. Kleeman et al and published in [11][12][13], where it was shown that the critical Li + concentration above which Downloaded by [Florida Atlantic University] at 21:43 02 February 2015…”
Section: Discussionsupporting
confidence: 93%
“…Thus the different nature of the low temperature phase for samples with x > 0.025 as compared to samples with x < 0.25 is clearly put in evidence. These results are in favour of a freezing of the Li+ ions (possibly of the quadrupoles only) in these low x samples as suggested previously from other measurements [7]. They are called orientational glasses.…”
Section: Phase Transitionsupporting
confidence: 82%
“…It can be interpreted as due to an ordering of the dipoles and of the quadrupoles, resulting in a lower symmetry. This structural change from a cubic symmetry at high temperature to a probably tetragonal symmetry at low temperatures has been inferred from other results of Raman scattering [5], X-ray scattering [6] and birefringence measurements [7,8] performed on samples with Li+ concentrations close to that of this sample. In the sample with a lower concentration (x = 0.015), the behaviour, shown in figure 1, is very different.…”
Section: Phase Transitionsupporting
confidence: 74%
“…Recently Tyunina et al [6] have reported strain-induced ferroelectric order in epitaxial thin film KTaO 3 . Doping KTaO 3 with Li þ ions, K 1À x Li x TaO 3 , causes a very complex polar behavior [1,[7][8][9][10][11][12][13][14][15][16][17][18]. In the case of x 4x cr % 0:02, [8,11], a ferroelectric state appears.…”
Section: Introductionmentioning
confidence: 99%